PENGARUH JENIS MEDIA PUPUK KANDANG DAN PEMBERIAN PUPUK ORGANIK CAIR DAUN LAMTORO TERHADAP PERTUMBUHAN BIBIT VANILI (Vanilla planifolia) - Abdurrahman Salim; Ujang Setyoko; Abdul Madjid; Hasyim Asyari (Jurnal Penelitian Pertanian Terapan, 2023)
Provision of nutrients is one of the important things in plant cultivation. One of the nutrients that can be obtained from organic fertilizers. Manure is one type of organic fertilizer that can increase soil nutrients. The manure used in the media is cow and goat manure. In addition to manure, the application of Liquid Organic Fertilizer (POC) of lamtoro leaves can also provide nitrogen elements in the soil. The element nitrogen has good benefits for nurseries because it can accelerate vegetative growth in plants. The purpose of this study was to determine the effect of adding manure media by giving lamtoro leaf POC to vanilla seeds. This research was carried out at the Jember State Polytechnic in July – November 2020. This study used a factorial randomized block design with two factors, namely the first factor was 3 types of planting media consisting of control, addition of cow kendang fertilizer and addition of cow kendang fertilizer. Then the second factor was giving lamtoro leaf liquid organic fertilizer with three levels consisting of control, 25%, and 50%.. The results showed that goat manure showed the best results in increasing shoot length, shoot diameter, leaf width and wet weight of vanilla plants. Application of liquid organic fertilizer with a concentration of 50% gave the best results for increasing shoot length, shoot diameter and wet weight of vanilla plants. Meanwhile, the interaction does not show a significant effect. Keywords:Lamtoro Leaves; Manure; POC; Vanilla plant